Lower threshold to NFκB activity sensitizes murine β-cells to streptozotocin. Issue 3 (6th May 2021) - Wright, Clyde J; McKenna, Sarah; De Dios, Robyn; Boehmer, Brit H; Nguyen, Leanna; Ghosh, Sankar; Sandoval, Jeryl; Rozance, Paul J
Abstract : The β-cell response to injury may be as critical for the development of diabetes as the specific insult. In the current study, we used streptozotocin (STZ) to injure the β-cell in order to study the response with a focus on NFκB. MIN6 cells were exposed to STZ (0.5–8 mM, 0–24h) ±TNFα (100 ng/mL) and ±IκBβ siRNA to lower the threshold to NFκB activation. Cell viability was determined by trypan blue exclusion. NFκB activation was determined by the expression of the target genes Nos2 and Cxcl10, localization of the NFκB proteins p65 and p50, and expression and localization of the NFκB inhibitors, IκBβ and IκBα. There was no NFκB activation in MIN6 cell exposed to STZ (2 mM) alone. However, knocking down IκBβ expression using siRNA resulted in STZ-induced expression of NFκB target genes and increased cell death, while co-incubation with STZ and TNFα enhanced cell death compared to either exposure alone. Adult male IκBβ −/− and WT mice were exposed to STZ and monitored for diabetes. The IκBβ −/− mice developed hyperglycemia and diabetes more frequently than controls following STZ exposure. Based on these results we conclude that STZ exposure alone does not induce NFκB activity. However, lowering the threshold to NFκB activation by co-incubation with TNFα or lowering IκBβ levels by siRNA sensitizes the NFκB response to STZ and results in a higher likelihood of developing diabetes in vivo . Therefore, increasing the threshold to NFκB activation through stabilizing NFκB inhibitory proteins may prevent β-cell injury and the development of diabetes.